Incremental vs. Disruptive Innovation Strategies: Comparative Effects on Organizational Performance in the Textile Industrial Sector - LAKHLIFI , Fatima Zahrae; ABDELLAOUI , Mohammed (Revue Internationale du Chercheur, 2024)
This article examines the comparative effects of incremental and disruptive innovations on organizational performance in the textile industrial sector, within the framework of Morocco’s industrial policy 2023-2030, which prioritizes innovation as a factor of competitiveness. A quantitative approach based on segmented correlation analysis was used to assess the impact of each type of innovation on productivity, cost reduction, quality and flexibility, taking into account company size, in the Casablanca-Settat region. The study is based on a sample of 174 companies, representing different sizes and sectors of the textile industry. The results show that company size has a decisive influence on the choice and impact of innovations adopted, as well as the performance criterion. The study highlights the importance of adapting innovation strategies according to company size in order to maximize profits, and opens up prospects for analyzing the long-term effects of these innovations and their application in other industrial sectors.